Frontier days diorama - Gordon, John C. (photographer):::Creator::::::::::::
Photograph shows a diorama of a frontier wooden cabin and fort. Above the diorama, some class reports on civics and U.S. government are on display. The sign in the diorama reads: "Frontier Days by 7th grade. Miss Heinbach."